2022
DOI: 10.1101/2022.06.15.22276457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy and Confidence in the Philippines and Malaysia: A Cross-sectional Study of Sociodemographic Factors and Information-Seeking

Abstract: With the emergence of the highly transmissible Omicron variant, large-scale vaccination coverage is crucial to the national and global pandemic response, especially in populous Southeast Asian countries such as the Philippines and Malaysia. Little is known, however, about predictors of COVID-19 vaccine hesitancy and vaccine confidence among unvaccinated individuals in these regions. An internet-based cross-sectional survey was conducted from May 2021 to September 2021. Data from a total of 2558 participants fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…Our study finds that Buddhists and other small religious groups, including Hindu, Animist, Taoist, Jewish, and Confucianist, have a higher self-reported tendency towards polio vaccine refusal than Catholics. This result contradicts previous literature where Buddhists were generally found to have high vaccine acceptance (46)(47)(48), but is consistent with previous research conducted in Western Pacific Region (49)(50)(51). The vaccine hesitancy among Buddhists could be explained by the incompatibility between Buddhist belief to harm no living things and misinformation on polio vaccine production (48).…”
Section: Discussionsupporting
confidence: 74%
“…Our study finds that Buddhists and other small religious groups, including Hindu, Animist, Taoist, Jewish, and Confucianist, have a higher self-reported tendency towards polio vaccine refusal than Catholics. This result contradicts previous literature where Buddhists were generally found to have high vaccine acceptance (46)(47)(48), but is consistent with previous research conducted in Western Pacific Region (49)(50)(51). The vaccine hesitancy among Buddhists could be explained by the incompatibility between Buddhist belief to harm no living things and misinformation on polio vaccine production (48).…”
Section: Discussionsupporting
confidence: 74%
“…A cross-sectional survey on Covid-19 vaccine hesitancy and confidence in the Philippines and Malaysia indicates a high prevalence of Covid-19 vaccine hesitancy. The same study also reveals that other factors negatively impacting confidence in the Covid-19 vaccines include rural dwellings, the Christian religion, and online information seeking [34].…”
Section: Discussionmentioning
confidence: 73%
“…The deleterious impacts of the global Covid-19 lockdowns on routine immunizations and the global Covid-19 vaccine hesitancy challenges are well documented across all regions of the world [11][12][13][14]. Findings from this study has revealed some critical Covid-19 implementation science gaps in Northern Nigeria.…”
Section: Discussionmentioning
confidence: 94%
“…Religion plays a vital role in the lives of the citizens of Nigeria as it affects all facets of social, political, and economic life. In a cross-sectional survey on Covid-19 vaccine confidence and hesitancy in the Philippines and Malaysia, religion was found as one of the factors negatively impacting confidence in the Covid-19 vaccine uptake [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation